2008
DOI: 10.1038/ng.134
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic approaches implicate osteoglycin (Ogn) in the regulation of left ventricular mass

Abstract: Left ventricular mass (LVM) and cardiac gene expression are complex traits regulated by factors both intrinsic and extrinsic to the heart. To dissect the major determinants of LVM, we combined expression quantitative trait locus1 and quantitative trait transcript2 (QTT) analyses of the cardiac transcriptome in the rat. Using these methods and in vitro functional assays, we identified osteoglycin (Ogn) as a major candidate regulator of rat LVM, with increased Ogn protein expression associated with elevated LVM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 30 publications
7
135
2
2
Order By: Relevance
“…Extensive exploration of inflammation, myofibroblast differentiation, and signaling, as well as cardiomyocyte cytoskeletal properties and hypertrophy could not reveal differences in these factors that could contribute to increased cardiac rupture, mortality, or failure in osteoglycin null mice. Although previous studies demonstrated a role for osteoglycin in cardiac hypertrophy after angiotensin infusion, 13 our data do not support a role for osteoglycin in cardiomyocyte hypertrophy. This may be because of the differences in the pathophysiology of the models.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Extensive exploration of inflammation, myofibroblast differentiation, and signaling, as well as cardiomyocyte cytoskeletal properties and hypertrophy could not reveal differences in these factors that could contribute to increased cardiac rupture, mortality, or failure in osteoglycin null mice. Although previous studies demonstrated a role for osteoglycin in cardiac hypertrophy after angiotensin infusion, 13 our data do not support a role for osteoglycin in cardiomyocyte hypertrophy. This may be because of the differences in the pathophysiology of the models.…”
Section: Discussioncontrasting
confidence: 55%
“…This may be because of the differences in the pathophysiology of the models. In the study performed by Petretto et al, 13 hypertrophy was assessed by LV mass rather than a histological analysis of cardiomyocyte cross-sectional area. Furthermore we, and others, have found that cardiac fibroblasts express high levels of osteoglycin as compared with cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there is strong evidence for heritability of LV mass, including observations from studies of the general population, 19 sibling studies, 20 and recent longitudinal twin studies, 21 considerable interest exists in identifying putative genetic risk factors that modulate LV mass. These efforts have progressed from candidate gene association studies 22 to genome-wide expression analyses with the use of microarray data 23 and genome-wide association studies 24 but remain in their relatively early stages and have not yet yielded results that have translated into the clinical arena. It seems likely that multiple variants, each with modest effect size, will be involved in modulating complex traits, 25 including LV mass.…”
Section: What Explains the Variability In The Development And Patternmentioning
confidence: 99%
“…The other noteworthy gene in this QTL is osteoglycin (OGN). In a quantitative trait transcript (QTT) analysis study of the cardiac transcriptome in the rat, Petretto et al [16] showed that OGN is a key regulator of left ventricular mass (LVM) in rats, mice and humans, and suggested that OGN modifies the hypertrophic response to extrinsic factors such as hypertension and aortic stenosis.…”
Section: Candidate Genes For the Qtl On Gene-rich And/or Gene-poor Chmentioning
confidence: 99%